PENGARUH PEMBERIAN AIR PERASAN JERUK NIPIS (CITRUS AURANTIFOLIA SWINGLE) TERHADAP KADAR KOLESTEROL PADA MENCIT HIPERKOLESTEROLEMIA - Pangestuti, Dewi (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Lime (Citrus Aurantifolia) contains of main flavonoid in limes, that is herperidin. Hesperidin can help reducing total Cholesterol level and has the property of hypercholesterolemic. Hypercholesterolemia is the main factor independent risk factor of coronary heart disease (CHD). This study intend to determine whether or not the effect od water lime extract orally with cholesterol level in the hypercholesterolemia mice. This isi an experimental study designed following randomize control design and post test only control group design by using 24 mice (Mus musculus) adult male strain DD Webster divided into 4 groups: control group (P0) that Given adlibitum, (P1) that given hypercholesterolemia 0,2 cc, (P3) that given hypercholesterolemia 0,2 cc and water lime extract 0,3 cc by gastric sonde once a day for 15 days. In the day46 mice are done neck dislocation. Data result was analyzed by One Way- Anova test and continuous and continued with post-hoc test. Result of this study showed that giving of water lime extract 0,3 cc orally per mice could reduced cholesterol level of mice hypercholesterolemia than giving water lime extract 0,1 cc orraly per mice.